2021
DOI: 10.1016/j.rmed.2021.106537
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1 alleles associate with hypercalcemia in sarcoidosis

Abstract: Background:The mechanisms behind and which patients are at risk of developing sarcoidosis associated hypercalcemia (SAHC) have not been addressed. Different human leukocyte antigen (HLA) alleles associate with disease phenotypes in sarcoidosis. Insights into associations between HLA alleles, clinical phenotype and calcium levels may provide clues to mechanisms behind SAHC and help monitoring patients at risk for SAHC. Aims and objectives: To identify any HLA-association with SAHC, and to phenotypically charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…It results due to an excess conversion of 25(OH) vitamin D to 1,25(OH) vitamin D by macrophage 1-a-hydroxylase within granulomas. Hypercalcemia itself has been shown to be associated with more severe disease phenotypes, and if hypercalciuria occurs, it predisposes to nephrolithiasis as well [6,8]. In light of this, it is imperative to remember that this mechanism of hypercalcemia is not specific to sarcoidosis, and so it is imperative that other etiologies be first considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It results due to an excess conversion of 25(OH) vitamin D to 1,25(OH) vitamin D by macrophage 1-a-hydroxylase within granulomas. Hypercalcemia itself has been shown to be associated with more severe disease phenotypes, and if hypercalciuria occurs, it predisposes to nephrolithiasis as well [6,8]. In light of this, it is imperative to remember that this mechanism of hypercalcemia is not specific to sarcoidosis, and so it is imperative that other etiologies be first considered.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis can also present with renal involvement, presenting as granulomatous interstitial nephritis and hypercalcemia [6,8]. Other extrapulmonary findings include ocular manifestations, most commonly uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive genetic studies have demonstrated that the HLA-DRB1 shared epitope contributes to risk across different populations, particularly in ACPA-positive RA patients [ 49 , 51 ]. The importance of these risk alleles is not limited to RA, as these HLA haplotypes are strongly associated with sarcoidosis (including Löfgren’s syndrome), obliterative bronchiolitis, and idiopathic bronchiectasis [ 11 – 15 , 52 ]. Moreover, HLA-DRB1 alleles are linked to more severe forms of sarcoidosis, including a higher burden of lung granulomas as well as extrapulmonary manifestations such as hypercalcemia and ocular disease [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these risk alleles is not limited to RA, as these HLA haplotypes are strongly associated with sarcoidosis (including Löfgren’s syndrome), obliterative bronchiolitis, and idiopathic bronchiectasis [ 11 – 15 , 52 ]. Moreover, HLA-DRB1 alleles are linked to more severe forms of sarcoidosis, including a higher burden of lung granulomas as well as extrapulmonary manifestations such as hypercalcemia and ocular disease [ 52 ]. Our findings demonstrating significant gene (DR4) by environment (ODE) outcomes, strongly suggest that this unique MHC determinant markedly skews the host response to air pollutants towards a more robust lung inflammatory phenotype, with features shared by RA-associated lung disease as well as other primary inflammatory lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported an increased risk for patients of White European ancestry, male sex and over 40 years of age. The average duration between sarcoidosis diagnosis and detection of hypercalcemia was 1.39 years, when it occurs it´s considered a progressive form of the disease [10].…”
Section: Access Demonstrated That Caucasians More Frequentlymentioning
confidence: 99%